2021
DOI: 10.1523/jneurosci.2853-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Responses during Proactive and Reactive Inhibition Are Differentially Impacted by Stress in Anorexia and Bulimia Nervosa

Abstract: The authors wish to thank the participants for their time and dedication to this project; the nursing staff and radiographers for assisting the study protocol; and Dr. Bram Zandbelt for sharing the stop-signal anticipation task code. They also thank the Beat eating disorder charity for advertising the study.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 71 publications
(106 reference statements)
2
10
0
Order By: Relevance
“…Both patient groups reported increased routines relative to the control group; however, automaticity scores were only increased in the BN group. We previously found that women with BN, but not AN-BP, in this cohort have impairments in proactive inhibition (2), and the present findings offer further evidence of distinct self-regulatory deficits across these two disorders. Nevertheless, nonsignificant group differences in slips-ofaction task performance highlights outstanding challenges in relation to our understanding of dysregulated learning in eating disorders and its neural correlates.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Both patient groups reported increased routines relative to the control group; however, automaticity scores were only increased in the BN group. We previously found that women with BN, but not AN-BP, in this cohort have impairments in proactive inhibition (2), and the present findings offer further evidence of distinct self-regulatory deficits across these two disorders. Nevertheless, nonsignificant group differences in slips-ofaction task performance highlights outstanding challenges in relation to our understanding of dysregulated learning in eating disorders and its neural correlates.…”
Section: Discussionsupporting
confidence: 77%
“…As a detailed explanation of the study protocol has been reported previously (2,34), we provide a summary here. Following a telephone screening, potential volunteers completed an outpatient screening session prior to scanning, which included body composition testing, blood sampling, cognitive testing and two, semi-structured clinical interviews [e.g., the SCID-5 (35) and EDE v16 (36)] to establish current diagnoses of AN-BP, BN and comorbid psychiatric conditions.…”
Section: Study Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased compulsivity, manifesting as compulsive restriction of food intake and compulsive exercise is also in line with previous research (Davis and Kaptein, 2006;Godier and Park, 2014), as well as a higher level of negative urgency impulsive, particularly in cohorts of heightened impulsivity during negative emotional states (e.g. binge/purging AN or BN) (Westwater et al, 2019). The increased level of PUI is also in line with previous research.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that the acute kind of stress which is typically induced in a laboratory or neuroimaging setting does not make patients with BN lose control. Indeed, a previous study finds that such acute stress does not reduce inhibitory control in patients with BN (51). However, studies in daily life do find that negative emotions such as stress increase before a BE episode in patients with BN (52,53).…”
Section: Discussionmentioning
confidence: 96%